Blue Skies, Blue Seas Air Pollution, Marine Plastics, and Coastal Erosion in the Middle East and North Africa. - Heger, Martin (MENA development report., 2022)
While economic and social indicators in many Middle East and North Africa (MENA) countries have improved over the past three decades, the region's blue natural assets-clean air, healthy seas, and coastlines-have degraded virtually everywhere. Air pollution levels in the region's cities are among the highest in the world. Per capita marine plastic pollution is among the highest in the world; coastal erosion rates are the second fastest in the world. These combined challenges threaten local communities, livelihoods, and economies. In fact, the economic cost of MENA's deteriorating skies and seas is estimated at more than 3 percent of GDP per year. This publication reviews integrated solutions that the authors identify as the "four I's": --Inform stakeholders about the sources of these challenges. --Provide incentives that improve environmental outcomes for the public and the private sector. --Strengthen institutions to lower air and plastic pollution and to mitigate uncontrolled development and erosion of coastlines. --Invest in abatement options and promote sustainable solutions. Restoring MENA's blue skies and seas will benefit the health, livelihoods, and incomes of residents. There will inevitably be trade-offs, but choosing a path of green growth will create jobs, diversify economies, and make the region a better place for current and future generations. The actions of policy makers today will shape the trajectory of economies and communities for decades to come.